IMPLEMENTATION OF DIGITAL MARKETING OF OM BEWOK COFFEE SHOP IN BRANDING ROBUSTA LOCAL COFFEE NATIVE TO BANTEN: IMPLEMENTASI PEMASARAN DIGITAL KEDAI KOPI OM BEWOK DALAM MEM-BRANDING KOPI LOKAL ROBUSTA ASLI BANTEN - Hafidz Hanafiah; Rendra Prasetya (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2021)
Industrial Era 4.0 has passed; it's time to adapt to society 5.0, where people use technology with a digital role as an unavoidable interaction. One of them is the coffee shop business, which began to be loved by coffee lovers or coffeeholic. The RACE framework and the AIDA Model aim to attract consumers. Like om bewok coffee shop that takes the theme of Banten coffee as a source of coffee that comes from the local, this shop has a message that Banten coffee turns out to exist in some places, although not all of them exist. Om bewok coffee shop has a distinctive logo and strong branding with the help of digital marketing. Qualitative research by conducting observations and interviews and literature studies on research objects in coffee shops om bewok. The results showed that om bewok coffee shop business has been running for two years by lifting coffee from its own area. As one of the coffee shop startups in Serang City, this shop uses the help of digital technology in branding and promoting its products and starting from the use of Google Business, WhatsApp Business, Social Media, email, website, Youtube. For delivery and order problems, you can order through GoFood or Grab and pay with a digital wallet or COD. They are collaborating with serang city government in terms of the legality of business license, Halal, p-IRT. As well as synergizing with coffee farmers, other coffee shop partners, as well as building relationships with youth communities in Serang City. Lastly, cooperate with Baznas related to the distribution of zakat with the help of QRIS or barcode. So powerful is digital marketing to build a relationship that is quite extensive